NORMAL MORPHOFUNCTIONAL AND HISTOLOGICAL STRUCTURE OF THE KIDNEYS - Kaymanova Kamila Imamovna (Scholars Digest Publishing, 2025)
The kidneys are vital organs that play a key role in maintaining homeostasis through filtration, excretion, and regulatory mechanisms. Understanding their normal morphofunctional and histological architecture is essential for both physiological and pathological studies. This literature review aims to summarize current knowledge on the anatomical, cellular, and functional organization of the kidneys under normal conditions. It explores the gross morphology, microanatomical features, and functional units such as nephrons, supported by recent histological and ultrastructural research. The review also addresses the renal cortex and medulla differentiation, glomerular structure, and tubular specialization, providing a foundational understanding for further nephrological and biomedical investigations.
Keywords: Kidney morphology, renal histology, nephron structure, renal physiology, glomerulus, tubular system, renal cortex and medulla.